Comparison of Cholesterol Levels Using Serum and Plasma Samples of EDTA Anticoagulants Using the CHOD-PAP Method - Agus Riyanto; Mona Megasari (Journal of Sustainability Science and Technology, 2022)
Health laboratory services or clinics can assist with patient recovery monitoring or diagnosis. The measurement of cholesterol levels is one of the frequent laboratory examinations. The CHOD-PAP enzymatic approach is the most used way to check your cholesterol levels. Plasma or serum is the test substance for cholesterol. Due to the presence of EDTA anticoagulant particles that will impact the test, the use of plasma is vulnerable to mixing with erythrocytes. This study used blood and plasma samples of EDTA anticoagulant to ascertain the variation in the outcomes of the average cholesterol levels. This research method compares two samples of EDTA anticoagulant—serum and plasma—in an analytical analysis using a comparative approach. According to the findings, there was a 1.12 percent difference between the average cholesterol levels in the serum sample (195.33 mg/dL) and the EDTA anticoagulant plasma sample (193.13 mg/dL). These findings indicate that there is no discernible difference in the cholesterol examination results obtained using EDTA anticoagulant-infused serum and plasma samples.